Recursos tecnológicos transformando a relação museu e público - SENA, Hellen Patrícia Cardias de (2019)
This work was developed within the research during graduation in Museology, held at the Art Museum of Bethlehem (MABE). The theme deals with technological resources in museums, from the study of one of the first digital user experiences to create visits to the exhibition space, developed by MABE. It aims to present reflections on the challenges of safeguarding access to heritage in digital media. Also through interviews with questionnaires, conducted with visitors, check the level of acceptance of new technological devices, inquiring mainly contribute in some way to the classroom visit in space and what it thinks about the use of new technologies by museums, in actions to the public.